THERAPEUTIC ROLE OF NIMESULIDE IN ACUTE PAIN: FROM FORMULATION TO IN VIVO STUDY - Vemula, Prasanth; Vadlamudi, Rangarao; Deekshitha, Vasana Naga Durga; Veerla, Gayathri; Patibandla, Jahnavi (International Journal of Pharma and Bio Sciences, 2026)
Nimesulide, a selective cyclooxygenase-2 (COX-2) inhibitor, is a promising therapeutic agent for acute pain management owing to its rapid onset of action, favorable pharmacokinetics, and improved safety profile compared to conventional non-steroidal anti-inflammatory drugs (NSAIDs). The present study aimed to develop and evaluate Nimesulide tablets, focusing on their Preformulation, formulation, and pharmacological performance. Pre-compression and post-compression parameters confirmed acceptable flow and compressibility properties, with tablets demonstrating uniform weight, optimal hardness, low friability, and rapid disintegration. Drug content analysis revealed >98% uniformity, while in vitro release studies showed nearly complete drug release within 30 minutes, suggesting suitability for immediate pain relief. UV-spectrophotometric calibration confirmed linearity in the 6–28 µg/mL range (R² > 0.99). Solubility studies indicated poor aqueous solubility but better solubility in ethanol and acidic media. In vivo evaluation using the tail flick method in Wistar rats demonstrated a significant increase in pain threshold, with latency times increasing from 2 seconds (baseline) to 27 seconds at 1-hour post-administration, confirming a potent analgesic effect. Overall, the results validate Nimesulide’s role as an effective and well-tolerated analgesic for acute pain management, supporting its clinical relevance in modern therapeutics.